Brexit in Italian Contemporary Literature: Città irreale (Unreal city) by Cristina Marconi, Brexit Blues (Brexit Blues) by Marco Varvello and La mia Brexit (My Brexit) by Francesco De Carlo - Karp, Karol (Porównania, 2021)
The subject of the article is the phenomenon of Brexit in contemporary Italian literature investigated on the basis of the texts published so far, in which it plays an important role. Three novels are analyzed: Città irreale by Cristina Marconi, Brexit Blues by Marco Varvello and La mia Brexit by Francesco De Carlo, from which emerges negative image of Brexit, set in the context of immigration, which is a special area of interest for the above-mentioned authors.